4
$\begingroup$

I want to prove this proposition:

Let $H$ be an Hilbert space and let $M,N$ closed subspaces of $H$. Let$P_M$ and $P_N$ orthogonal projections with range(M) and range(N) respectively. Prove that $P_M + P_N = P_{M+N}$ if and only if $M \perp N$.

According to what I have studied in Regression analysis and linear algebra, I understand this proposition perfectly and my geometrical imagination capacity says that it is something obvious, but I don't know how to prove it, nethier how to start the proof (For me, this is just by definition of projection).

$\endgroup$
3
$\begingroup$

Suppose first that $M\perp N$. Then, for any $x,y\in H$, $$ \langle P_MP_Nx,y\rangle=\langle P_Nx,P_My\rangle=0. $$ As we can do this for all $x,y$, we get that $P_MP_N=0$. Then $$ (P_M+P_N)^2=P_M^2+P_N^2=P_M+P_N $$ and $P_N+P_M$ is a projection. Given $x+y\in M+N$ with $x\in M$ and $y\in N$, $$(P_M+P_N)(x+y)=P_Mx+P_Nx+P_My+P_Ny=x+y,$$since $P_Mx=x$, $P_nx=0$, $P_My=0$, $P_Ny=y$. If $z\in (M+N)^\perp$, then $$\langle(P_M+P_N)z,w\rangle=\langle z,(P_M+P_N)w\rangle=0.$$ So $P_M+P_N=P_{M+N}$.

Conversely, if $P_M+P_N=P_{M+N}$, then $$ P_M+P_N=P_{M+N}=P_{M+N}^2=P_M+P_N+P_NP_M+P_MP_N. $$ Then $$\tag{*}P_MP_N+P_NP_M=0.$$ Multiply on the left by $I-P_M$, and we get $(I-P_M)P_NP_M=0$. This is $P_MP_NP_M=P_NP_M$. Then $$ P_MP_N=(P_NP_M)^*=(P_MP_NP_M)^*=P_MP_NP_M=P_NP_M. $$ Then $P_NP_M=P_MP_N$ and now $(*)$ becomes $P_MP_N=0$. If we take $x\in M$ and $y\in N$, $$ \langle x,y\rangle=\langle P_Mx,P_Ny\rangle=\langle P_NP_Mx,y\rangle=0. $$ So $M\perp N$.

$\endgroup$
  • $\begingroup$ I'm trying to understand the proof now :) Thanks you for your answer. $\endgroup$ – Applicable Math Oct 8 '16 at 16:29
  • $\begingroup$ Sorry for commenting on such an old answer. I was wondering if when we assume $M\perp N$, is it obvious that $M+N$ is closed in the first place, so that $P_{M+N}$ is well defined? Is this implied somewhere within your proof, or would one need to prove this separately? $\endgroup$ – lkjhgfdsa Mar 13 '18 at 12:11
  • 1
    $\begingroup$ It is more or less obvious. If $z_n=x_n+y_n$ is Cauchy, from $\|z_n\|^2=\|x_n\|^2+\|y_n\|^2$ you get that each command is Cauchy. $\endgroup$ – Martin Argerami Mar 13 '18 at 14:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.